2019
DOI: 10.1016/s2665-9913(19)30050-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of social support with patient-reported outcomes after joint replacement: a systematic review and meta-analysis

Abstract: Is social support associated with patient-reported outcomes after joint replacement? A systematic review and meta-analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 92 publications
1
9
0
Order By: Relevance
“…Living alone and social isolation was greater in this study population and among patients undergoing arthroplasty. 10,33 Social support is defined as the provision of psychological and material resources within a social network. the use of these resources can be an important factor in obtaining positive outcomes, and has been shown to have a protective effect on general health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Living alone and social isolation was greater in this study population and among patients undergoing arthroplasty. 10,33 Social support is defined as the provision of psychological and material resources within a social network. the use of these resources can be an important factor in obtaining positive outcomes, and has been shown to have a protective effect on general health.…”
Section: Discussionmentioning
confidence: 99%
“…the use of these resources can be an important factor in obtaining positive outcomes, and has been shown to have a protective effect on general health. 33,34 social support has a multidimensional nature not captured when dichotomizing patients according to cohabitation status. 35 however, even by using this crude estimate, we found a higher risk of any infection after both 30 and 90 days when living alone, and when assessing the risk of pneumonia, UTI, and PJI specifically, although these estimates have large ci.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the beneficial impact of family support on postoperative outcomes has been previously demonstrated, with higher scores on a family cohesion scale being associated with better postsurgical recovery after open cholecystectomy [ 17 ]. In addition, a recent systematic review noted an association of social support and improved patient-reported outcomes after joint replacement [ 18 ]. In the United States, December holds major holidays, during which families gather and time off is provided from work and school [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pooled data from two studies comprising 2,022 lower limb arthroplasty recipients suggested that patients who had social support at one-year post-THR benefitted in terms of their function measured as WOMAC score [31].…”
Section: Social Supportmentioning
confidence: 99%